1987
DOI: 10.1007/bf01892350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilization on the nutritional quality of wheat variety, Yecora Rojo

Abstract: The effects of N-fertilization on the nutritional quality of short-straw wheat variety, Yecora Rojo, was studied under sprinkler irrigation system, The fertilizers applied were the conventional N-fertilizer, urea (U) applied as single dose or in three split applications (U-S), and the slow release N-fertilizers, ureaform (UF) (38% N and 20 N), osmocote (OC) with 9 or 14 months longevity and sulphur-coated urea (SCU) with either 17% or 37% dissolution rates in 7 days. These fertilizers were applied at 0 (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Our study indicated a strong effect of N and S fertilization on PC and PY production. These results were consistent with previous findings in 'modern' common wheat varieties [45][46][47][48][49]. Likewise, Guerrini et al (2020) [7] reported that S and N fertilization substantially affected the PC in 'old' varieties.…”
Section: Discussionsupporting
confidence: 92%
“…Our study indicated a strong effect of N and S fertilization on PC and PY production. These results were consistent with previous findings in 'modern' common wheat varieties [45][46][47][48][49]. Likewise, Guerrini et al (2020) [7] reported that S and N fertilization substantially affected the PC in 'old' varieties.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, this process is an added advantage at this stage since there are less nitrogen losses from the field hence reducing the farmers' production costs. In another research [26], it was found out that slow release fertilisers like urea led to a significant increase in grain protein content of cereals crops such as the wheat and rice. The slow release N fertilisers are effective in maintaining a balanced uptake of applied N that matches the needs of the crop at different growth stages.…”
Section: Grain Crude Protein As Affected By Nitrogen Forms and Levelsmentioning
confidence: 99%
“…Thus combinations of organic matter and nitrogen fertilizer would increase crop growth and grain yield. It is largely accepted that nitrogen fertilization affects protein content and composition and directly influences the technological quality of wheat 4–6. It is essential, therefore, to emphasize this concept of stability of quality in response to various levels of nitrogen fertilization in light‐textured sandy soils.…”
Section: Introductionmentioning
confidence: 99%